PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. UNILAB PERDANA - Azizah Rahmawati; Darlius (Jurnal Satya Mandiri Manajemen dan Bisnis, 2018)
This research uses employee’s performance as dependent variable, leadership, organizational culture and competence as independent variable. The analysis used included validity test, reliability test, classical assumption test, model test and linear regress ion analysis. The data is processed by using SPSS 20 program. Based on F count data (24,710)> F table (3,009) and significance <0,05 (0,000 <0,05), then H0 is rejected. So it can be concluded that Leadership, Organizational Culture and Competence together have a significant effect on employee’s performance. Based on the output R2 value is 0.420, it means that the percentage contribution of Leadership, Organizational Culture, and Competence variables against employee’s performance achievement is 42.0%, while the remaining 58.0% influenced by other variables that are not researched.